“O write in brasse”: George Herbert’s trajectory from pen to print - Anne-Marie Miller-Blaise (Etudes Epistémè)
Acts of writing, and even more so of blotting, are well known to the reader of George Herbert’s Temple as the poet struggles to make his ink and tears a form of imitative art for Christ’s sacrifice. Less attention has been given to the ways in which Herbert participates in the history of publication. Such a reticence can easily be accounted for by the fact that The Temple was printed posthumously. However, renewed interest in a biographical approach of Herbert has drawn attention to his relationship to the poetical coterie formed by the Sidney-Pembroke circles and their modes of aristocratic, scribal publication. This paper will attempt to examine how, though his poetry is modeled on Philip Sidney’s both plain and reflexive style, Herbert dramatizes and gradually dissociates from the modes of publication of his milieu, turning towards the horizon of print even for his private, devotional verse. I will argue that the dissemination of the printed letter better responded to Herbert’s aesthetic and theological design.